Representation of women in the lyrics of Cha-Cha songs a critical discourse analysis of selected Waray-Waray songs - Alfonso, Janielle Rose T. (2023)
Music has always reflected people's perspectives, emotions, and values; it reveals cultural identities, historical backgrounds, and various social dispositions. Lyrics in music, on the other hand, have been thought to fulfill a variety of roles. This thesis set out to examine the women in the lyrics of the Waray-Waray cha-cha songs entitled ?Pigsote?, ?Pikahi?, ?Birahe?, and ?Turutanding?. The main aims of this study were to: (1) identify the elements presented in the selected Waray-Waray cha-cha songs, (2) unravel how the themes are presented in the selected Waray-Waray cha-cha songs, and (3) discover how discourse plays in the depiction of women in the lyrics of the popular Waray-Waray cha-cha songs. Employing the Critical Discourse Analysis Theory during the investigation of media texts, the study discovered that the three songs established a good communicative occurrence since they have met the seven standards of textuality: cohesion, coherence, intentionality, acceptability, situationality, informativity, and intertextuality. This study discovered that the themes of the Waray-Waray cha-cha songs were communicated through the use of sexual innuendos, sensuous descriptive phrases, and sexual metaphors directed towards women. Additionally, by integrating the perspectives of Muted Group Theory and Cultivation Theory, it was able to determine the essence of discourse in revealing the pervasive and frequently hidden systems of beliefs, standards, and ideals that women receive from the way they are portrayed in the lyrics of the Waray-Waray songs.